Detection Of Biofilm Formation By Beta- Lactam Resistance Klebsiella Pneumoniae Isolated From Clinical Specimens And Aquatic Samples (Journal of the College of Basic Education, 2024)
Klebsiella pneumoniae causes a wide range of infection and it is found in different natural habitats like surface waters. It has become increasingly resistant to antibiotics, and the capacity of these bacteria to form biofilm is well known. This study aimed to determine the pattern of antibiotic resistance and biofilm-forming ability of K. pneumoniae isolated from clinical specimens and aquatic samples. Sixty- six (20.625%) Klebsiella pneumoniae clinical isolates were isolated from 320 clinical samples from Medical City Iraq, Baghdad. A total of 27 (18%) water isolates were gathered from 150 different water sources in the city of Baghdad. HiCrome UTI agar and biochemical testing were used to identify every isolate. The results show that the clinical isolates were more resistance to beta lactam antibiotics than water isolates and both of them were (100 %) resist to Amoxiclav. The resistance percentage of the clinical isolates was (6.06%) Meropenem, (13.63%) Imipenem, (19.69%) Ceftazidime, (53.03%) Cefotaxime and (86.36%) Ceftriaxone, while the resistance percentage for the water isolates was zero for the Meropenem, Imipenem, Ceftazidime, Cefotaxime and Ceftriaxone. The infB gene was used in molecular analysis to identify the beta- lactam antibiotic resistant isolates, and microtiter plate analysis was used to determine which isolates were most capable of forming biofilms. The results show a significant difference between biofilm formations among clinical and aquatic isolates and the aquatic isolates were more than clinical isolates in biofilm formation. The biofilm formation percentage among the most resistant for beta- lactam clinical isolates was (1 isolate (10%) strong, 2 isolates (20%) moderate, and 7 isolates (70%) weak), while the percentage for aquatic isolates was (2 isolates (20%) strong, 5 isolates (50%) moderates, and 3 isolates (30%) weak). This study showed that the aquatic isolates of K. pneumoniae are more than clinical beta- lactam resistant isolates in biofilm formation.